2020
DOI: 10.3390/foods9020157
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of L. monocytogenes and S. typhimurium Biofilms by Means of an Air-Based Cold Atmospheric Plasma (CAP) System

Abstract: Previous (biofilm) inactivation studies using Cold Atmospheric Plasma (CAP) focused on helium (with or without the addition of oxygen) as feeding gas since this proved to result in a stable and uniform plasma. In industry, the use of helium gas is expensive and unsafe for employees. Ambient air is a possible substitute, provided that similar inactivation efficacies can be obtained. In this research, 1 and 7 day-old (single/dual-species) model biofilms containing L. monocytogenes and/or S. typhimurium cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The high amounts of generated ROS in the presence of oxygen are, on the other hand, more vulnerable to quenching. As a result, their higher generation rate is (partially) nullified [38]. Thirdly, the absence of H 2 O 2 molecules following 10 min of CAP treatment does not necessarily mean that this species was not formed over the course of the treatment since H 2 O 2 can further react with other molecules to form other reactive CAP species.…”
Section: Generation Of Ros/rnsmentioning
confidence: 99%
“…The high amounts of generated ROS in the presence of oxygen are, on the other hand, more vulnerable to quenching. As a result, their higher generation rate is (partially) nullified [38]. Thirdly, the absence of H 2 O 2 molecules following 10 min of CAP treatment does not necessarily mean that this species was not formed over the course of the treatment since H 2 O 2 can further react with other molecules to form other reactive CAP species.…”
Section: Generation Of Ros/rnsmentioning
confidence: 99%
“…Thus, the study of new tools for the control of bacterial biofilms has increased lately, focusing on novel technologies, such as cold atmospheric plasma [12], or natural antimicrobials. Among these natural antimicrobials, essential oils (EOs) have always been among the best options to choose as they come from edible plants that have been consumed by humanity since ancient times.…”
Section: Introductionmentioning
confidence: 99%
“…Cold atmospheric plasma has also been proven to be a promising strategy for the control of multispecies biofilms formed by foodborne pathogens (Govaert et al, 2020;Huang et al, 2020). The cultures of S. Typhimurium mixed with cultivable indigenous microorganisms exhibited greater resistance to cold oxygen plasma (COP) compared with monoculture biofilms on fresh iceberg lettuce (Jahid et al, 2015).…”
Section: Food Industrial Applicationsmentioning
confidence: 99%
“…The inoculation on lettuce required an extended time to complete the eradication of mixed-species biofilms, and L. monocytogenes and P. fluorescens reduced by 2.2 and 4.2 log10 CFU/ml, respectively, after 120 s of contained treatment. Govaert et al (2020) reported the air-based CAP treatment of dual-species biofilms formed by L. monocytogenes and S. Typhimurium, and a result of log10 CFU/cm 2 -reductions ranging between 1.5 and 2.5 was observed. The inactivation efficacy of CAP treatment may depend on the biofilm population type, but not the working gas supplied ( Table 2).…”
Section: Food Industrial Applicationsmentioning
confidence: 99%